Advocacy Disabled in Publishing Newspapers Media in Malaysia - Hazzlan Sama; Manisah Binti Mohd Ali (Department of Special Education, 2017)
This article discusses the role of news media in communicating information about Disabled news to the public. The focus of the discussion centered issue and advocacy role of the news media conducted to understand the issues of persons with disabilities. Studies conducted using the method of analysis to systematically review the library of selected journals that conduct media exposure of persons with disabilities at the global level and so focused towards media conference in Malaysia. In this research, the data was obtained through databases ERIC, google scholar, Journal of Education, Journal of Social Sciences and Journal of Communication. A total of 30 articles were based on keywords such as disabled people, newspapers, news exposure to people with disabilities. However, researchers have obtained 13 articles that met after being filtered. The results obtained showed that the press releases are also still not open and not to report the news on disabilities. This is because there is a stigma that prevents acceptance of disabilities such as discrimination and negative attitudes towards them. Outlook negative stereotypes of people with disabilities who are strangers, the great ones, defects often appear in the media. Even now there is increasing advocacy for press media publishing news on this special group but the content or dissemination of information about them is still less show.Artikel ini membincangkan peranan media akhbar dalam menyampaikan maklumat berita tentang Orang Kurang Upaya kepada masyarakat. Fokus perbincangan ditumpukan isu dan peranan advokasi media akhbar dijalankan untuk memahami isu orang kurang upaya. Kajian yang dijalankan menggunakan kaedah analisis perpustakaan secara sistematik review terhadap jurnal-jurnal terpilih yang menjalankan kajian paparan media ke atas orang kurang upaya di peringkat global dan seterusnya difokus ke arah media akhbar di Malaysia. Dalam penyelidikan ini, data-data diperolehi melalui pengkalan data ERIC, google scholar, Jurnal Pendidikan, Jurnal Sains Sosial dan Jurnal Komunikasi. Sebanyak 30 artikel diperolehi berdasarkan kata kunci seperti orang kurang upaya, surat khabar, paparan berita terhadap OKU. Namun begitu, penyelidik telah memperoleh 13 artikel yang menepati setelah disaring. Hasil didapati menunjukkan akhbar akhbar juga masih tidak terbuka dan kurang untuk melaporkan berita tentang OKU. Ini kerana masih terdapat stigma yang menghalang penerimaan OKU seperti diskriminasi dan sikap negatif terhadap mereka. Pandangan stereotaip golongan OKU yang negatif seperti orang asing, golongan yang susah, cacat sering dipaparkan dalam media. Walaupun, kini media akhbar ada peningkatan advokasi penerbitan berita terhadap golongan istimewa ini namun kandungan atau penyebaran maklumat tentang golongan ini masih lagi kurang dipaparkan.DOI: http://dx.doi.org/10.17977/um029v4i12017p032